2013
DOI: 10.1007/s00253-013-5128-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression and delivery of an endolysin to combat Clostridium perfringens

Abstract: Clostridium perfringens is a cause for increasing concern due to its responsibility for severe infections both in humans and animals, especially poultry. To find new control strategies to treat C. perfringens infection, we investigated the activity and delivery of a bacteriophage endolysin. We identified a new endolysin, designated CP25L, which shows similarity to an N-acetylmuramoyl-l-alanine amidase domain and is distinct from other C. perfringens endolysins whose activity has been demonstrated in vitro. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 56 publications
2
50
0
Order By: Relevance
“…The endolysins are highly specific to the host bacterium (genus) and have evolved to bind to unique and essential bacterial cell wall targets. In recent years, phage endolysins have attracted considerable interest as novel antibacterial agents (18) and have been used to treat a variety of bacterial infections, as demonstrated by the increasing number of experimental animal studies (19)(20)(21)(22). Similarly, human studies have documented the use of live antistaphylococcal phages for the treatment of conjunctivitis and blepharitis in 28 patients, with no side effects (23,24).…”
mentioning
confidence: 99%
“…The endolysins are highly specific to the host bacterium (genus) and have evolved to bind to unique and essential bacterial cell wall targets. In recent years, phage endolysins have attracted considerable interest as novel antibacterial agents (18) and have been used to treat a variety of bacterial infections, as demonstrated by the increasing number of experimental animal studies (19)(20)(21)(22). Similarly, human studies have documented the use of live antistaphylococcal phages for the treatment of conjunctivitis and blepharitis in 28 patients, with no side effects (23,24).…”
mentioning
confidence: 99%
“…perfringens strains in vitro and a limited level of cross species activity against a strain of B. cereus and B. subtilis (Gervasi et al . ).…”
Section: Application Of Bacillus and Clostridium‐derived Phages And Ementioning
confidence: 97%
“…The expression of a Cl. perfringens endolysin (CP25L) within a probiotic Lactobacillus lactis strain presents an interesting alternative to the use of a replicating phage cocktail (Seal 2013;Gervasi et al 2014) and has demonstrated activity against multiple Cl. perfringens strains in vitro and a limited level of cross species activity against a strain of B. cereus and B. subtilis (Gervasi et al 2014).…”
Section: Application Of Bacillus and Clostridium-derived Phages And Ementioning
confidence: 99%
“…or gut bacteria. The recombinant probiotic was used for delivering the endolysin to the gastrointestinal tract of poultry where the active endolysin was efficiently secreted, suggesting that it may be helpful for controlling enteric clostridiosis (Gervasi et al, 2013b). Recently, a newly-identified specific anticlostridial phage endolysin CP25L was derived from a C. perfringens prophage (Gervasi et al, 2013a).…”
Section: Bacteriophagesmentioning
confidence: 99%